A novel technique of dynamic speed control for buck boost converter fed BLDC motor drive - Sasikala, K; Krishna Kumar, R (International Journal of Engineering and Technology, 2018)
This paper mainly impacts on a bridgeless buck boost converter fed Brush Less Direct Current (BLDC) motor drive with Power Factor Correction (PFC) which is low cost and well suitable for low power applications. The speed of the BLDC motor is controlled by adjusting the Voltage Source Inverter’s dc link voltage which is then employed along with a distinct voltage sensor. Thus the fundamental frequency switching of VSI operation becomes quite ease with BLDC motor’s electronic turn off which provides minimal switching losses. An acceptable performance is attained for speed control having power quality indicators within the allowable limits. To end with the suggested drive’s prototype model has been implemented to evaluate and confirm the suggested BLDC motor drive’s performance for various speed controls with enhanced AC main’s power quality.